THE PROBABILITY OF CALCULATING THE POLLUTION LIMIT IN MINERAL-CONTAMINATED (PB ,CR, CU) IN THE INTEGRATED ECOSYSTEM IN THE CONTROLLING HEADQUARTERS /AL- MUTHANNA MILITARY AIRPORT – BAGHDAD (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Globally, pollution is a problem that might have unfavorable outcomes. It is crucial to consider the main causes of soil contamination, such as the integrated ecosystem in the command center at the Al-Muthanna military airport in Baghdad, when trying to solve this problem. The current study's main objectives were to determine whether it was possible to calculate the pollution limit in mineral-contaminated soils and the impact of nearby plants on the air. Following three periods of sampling at three key locations, including the area and leaf of Eucalyptus camaldulensis, many components and variables, including (Pb ,Cr, Cu). Traceable elements were measured and chemically obtained utilizing x-ray fluorescence due to the site's exposure. When samples were digested for a control factor restricting the PTL threshold, materials were examined using ICPES for the qualitative detection of these components. The relative proximity (RP), which is determined by dividing the ICPES value by the sample's XRF values, indicates how close an element is to the sample. Sites 2 and 1, respectively, measured the component's biodegradability, and areas 2 and 3 revealed the highest values. Its plant uptake is 26%, 10%, and 7% in the order of Pb, Cr, and Cu. The data collected show that the integrated ecosystem at the command center and Al-Muthanna military airport in Baghdad has a high potential for contamination.